2021
DOI: 10.1177/10105395211011012
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on First Nations People Health Assessments in Australia

Abstract: The COVID-19 (coronavirus disease 2019) pandemic has the potential to worsen existing health inequalities faced by Aboriginal and Torres Strait Islander peoples in Australia. We aimed to assess the impact of the pandemic on First Nations people health assessments using an interrupted time series model utilizing data extracted from the Australian Medicare Benefits Schedule database. Additive triple exponential smoothing was used to model health assessments undertaken between January 2017 and December 2019. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(12 reference statements)
0
3
0
1
Order By: Relevance
“…Factors hypothesised to be associated with vaccine uptake among PWID were assessed. Demographic characteristics included in the model were gender [24], sexual identity [25], age [26], Aboriginal and Torres Strait Island background [27], and language spoken at home by parents [4]. The following variables were also hypothesised to be associated with vaccine uptake: HIV and HCV antibody serostatus [28,29], frequency of injection and drug last injected as a proxies for severity of substance use disorder and possible indicators of structural barriers to accessing health care [30], and current opioid agonist therapy (OAT) and recent (past year) imprisonment given the potential for greater access to health professionals to facilitate vaccination in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…Factors hypothesised to be associated with vaccine uptake among PWID were assessed. Demographic characteristics included in the model were gender [24], sexual identity [25], age [26], Aboriginal and Torres Strait Island background [27], and language spoken at home by parents [4]. The following variables were also hypothesised to be associated with vaccine uptake: HIV and HCV antibody serostatus [28,29], frequency of injection and drug last injected as a proxies for severity of substance use disorder and possible indicators of structural barriers to accessing health care [30], and current opioid agonist therapy (OAT) and recent (past year) imprisonment given the potential for greater access to health professionals to facilitate vaccination in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…One study ( 23 ) reported on engagement levels during 2011–2012, 1,169 health checks completed in Orange. However, there are also contradictory findings explored in a research conducted by Robertson et al ( 26 ) which demonstrated statistically significant reductions in total First Nations people’s health assessments during the early wave of COVID-19 (March, April, and May 2020).…”
Section: Resultsmentioning
confidence: 95%
“… [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] ...…”
Section: Uncited Referencesunclassified
“…Although such changes have been effective, they may inadvertently lead to health inequality. For example, cultural barriers preclude many of Australia's First Nations peoples from engaging with telehealth,(12) whilst public health messages have not always been optimally conveyed to nonemergencies and CNS tumours with the potential for quick deterioration (16). In some centres, RTonly therapy was instituted whenever there was thought to be clinical equipoise, allowing patients to avoid surgery (17).…”
mentioning
confidence: 99%